Assessment of Tissue Oxygenation and Radiation Dermatitis Pre-, During, and Post-Radiation Therapy in Breast Cancer Patients - Robledo, Edwin A.; Murillo, Juan; Martin, Raquel Veiga; Leiva, Kevin; Beiner, Corina; Rodrigues, Maria Amelia; Fagundes, Marcio; Panoff, Joseph; Chuong, Michael; Wu, Wensong; Godavarty, Anuradha (Frontiers in Oncology, 2022)
Over 95% of breast cancer patients treated with radiation therapy (RT) undergo an adverse skin reaction known as radiation dermatitis (RD). Assessment of severity or grading of RD is clinically visual and hence subjective. Our objective is to determine sub-clinical tissue oxygenation (oxygen saturation) changes in response to RT in breast cancer patients using near-infrared spectroscopic imaging and correlate these changes to RD grading. A 4-8 week longitudinal pilot imaging study was carried out on 10 RT-treated breast cancer patients. Non-contact near-infrared spectroscopic (NIRS) imaging was performed on the irradiated ipsilateral and the contralateral breast/chest wall, axilla and lower neck regions before RT, across the weeks of RT, and during follow-up after RT ended. Significant changes (p < 0.05) in oxygen saturation (StO2) of irradiated and contralateral breast/chest wall and axilla regions were observed across weeks of RT. The overall drop in StO2 was negatively correlated to RD scaling (in 7 out of 9 cases) and was higher in the irradiated regions when compared to its contralateral region. Differences in the pre-RT StO2 between ipsilateral and contralateral chest wall is a potential predictor of the severity of RD. The subclinical recovery of StO2 to its original state was longer than the visual recovery in RD grading scale, as observed from the post-RT assessment of tissue oxygenation.